Konsep Perkawinan yang Bertanggung Jawab dalam Perspektif Zakiah Daradjat - Ahmad Putra; Roy Bagaskara (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2020)
This paper explains the importance of instilling a responsible attitude in undergoing marital relations. Someone who has matured to enter the realm of marriage / marriage should understand the purpose and purpose of a marriage that he will take. Zakiah Daradjat in this case said that marriage is not an easy matter, but each family member has their respective rights and obligations, has roles and responsibilities. If responsibilities are not carried out properly, then it is not impossible that problems will easily come and damage the blessing of a marriage. In fact, marriage teaches the meaning of a responsibility, without responsibility the harmony in the family cannot be achieved so that it leads to a broken marriage relationship. This is the reason that can prevent a family from disputes and disputes so that families built through marriage reach the degree of sakinah, mawaddah, warahmah and blessed by Allah SWT. Tulisan ini menjelaskan tentang pentingnya menanamkan sikap tanggung jawab dalam menjalani hubungan perkawinan.Seseorang yang telah matang untuk masuk pada ranah perkawinan/pernikahan hendaknya memahami tujuan dan maksud dari sebuah perkawinan yang akan ia tempuh. Zakiah Daradjat dalam hal ini menyampaikan bahwa perkawinan bukanlah sebuah perkara yang mudah, akan tetapi setiap anggota keluarga mempunyai hak dan kewajibannya masing-masing, memiliki peran dan tanggung jawab. Jika tanggung jawab tidak terlaksana dengan sebagaimana mestinya, maka bukan tidak mungkin permasalahan akan mudah datang dan merusak keberkahan sebuah perkawinan.Sejatinya, perkawinan mengajarkan arti sebuah tanggung jawab, tanpa tanggung jawab maka keharmonisan dalam keluarga tidak akan dapat diraih sehingga membawa kepada retaknya hubungan perkawinan. Alasan inilah yang dapat menghindarkan sebuah keluarga dari percekcokan dan perselisihan agar keluarga yang dibangun melalui perkawinan mencapai derajat sakinah, mawaddah, warahmah serta diridhai oleh Allah SWT.